Influence of Controller High Pass Filter on the Performance of Shunt Hybrid Power Filter - Jamali, S.; Masoum, Mohammad; Mousavi, S. (University of New South Wales, 2008)
This paper presents an investigation on influence of the control system high pass filter characteristics on the performance of the shunt hybrid power filter. The power filter is consisting of a shunt passive filter connected in series with an active power filter. Frequency response of the shunt hybrid power filter, tacking into account the effect of high pass filter (used in control system for extracting harmonic components of the source current) is investigated by mathematical analysis. Computer simulations for a typical distribution system including a thyristor controlled rectifier and a shunt hybrid power filter have been carried out to validate the presented analysis. Harmonic contents of the source current have been calculated and compared for different cases to demonstrate the influence of harmonic extraction circuit on the harmonic compensation characteristics of the shunt hybrid power filter.